Revision of Pleuroprion zur Strassen, 1903 (Holidoteidae) and re-evaluation of Spectrarcturus Schultz, 1981 (Arcturidae) (Crustacea, Isopoda, Valvifera) - Stransky, B.; Svavarsson, J.; Poore, G. C.; Kihara, T. C. (Zootaxa, 2020)
Pleuroprion zur Strassen, 1903 is revised and restricted to its type species, Antares chuni zur Strassen, 1902, which is redescribed, using the type material from the German Deep-Sea Expedition in 1898–1899 and more recent material. Pleuroprion is transferred to Holidoteidae Wägele, 1989. Pleuroprion frigidum Hansen, 1916 is transferred to Astacilla Cordiner, 1793 (Arcturidae), while all other species previously placed in Pleuroprion, i.e. P. murdochi (Benedict, 1898), P. chlebovitschi Kussakin, 1972, P. fabulosum Gujanova, 1955, P. furcatum Kussakin, 1982, P. hystrix (Sars, 1877), P. intermedium (Richardson, 1899), P. iturupicum Kussakin & Mezhov, 1979 and P. toporoki Kussakin, 1972, are transferred to Spectrarcturus Schultz, 1981 (Arcturidae). The type species of Spectrarcturus, S. multispinatus Schultz, 1981, is a subjective junior synonym of Arcturus murdochi Benedict, 1898, now S. murdochi comb. nov. Spectrarcturus murdochi (Benedict, 1898) is redescribed on the basis of its type material and new material from South Greenland.